Clinical course and outcomes of patients presenting with traumatic zone 3 scleral lacerations with complete versus incomplete laceration closure during the primary repair - Tetelbom, Pedro; Chauhan, Muhammad Z.; Uwaydat, Sami H. (Digital Journal of Ophthalmology, 2024)
Introduction Posterior zone 3 scleral lacerations (SL) may require excessive manipulation to close, which may exert unintended pressure on the globe. In this study, we compare the clinical course and outcomes of complete versus incomplete closure of zone 3 SL. Methods We reviewed the medical charts of consecutive patients with zone 3 SL who underwent globe exploration and repair, followed by PPV for the management of traumatic vitreoretinal sequelae between 2010 and 2022. Demographic, preoperative, surgical, and postoperative data were recorded. Patients with zone 3 SL and follow-up of at least 3 months from the initial injury were included. Cases were subdivided into complete and incomplete closure groups, based on the operative note details. Results A total of 36 patients (29 males [81%]) were included. Mean age of was 46.47 ± 17.45 years. Fourteen (39%) had incomplete zone 3 SL repair. The incomplete and complete repair groups had similar presenting visual acuity, time to initial repair and time to first PPV. There was no statistical difference between the 2 groups with respect to the total number of surgeries, and visual acuity at last follow-up. Silicone oil use on subsequent surgeries was similar between the two groups (P = 0.09). Proliferative vitreoretinopathy (OR 0.58 [CI, 0.12-2.78]) was not associated with an incomplete closure. 3 eyes were enucleated, all from the complete closure group. The retina was attached without oil at last follow-up at similar rates (OR = 0.62 [CI, 0.16-2.41]) between the two groups. There were no recorded cases of postoperative endophthalmitis in this series. Conclusions Our results show that incomplete closure of globes with a zone 3 SL carry a similar prognosis compared to eyes that underwent complete closure of the SLs. We hypothesize that aggressive attempts at closing posterior SLs may not add benefit to the postoperative outcomes.